Impaired Recycling of Apolipoprotein E4 Is Associated with Intracellular Cholesterol Accumulation - Jöerg Heeren; Thomas Grewal; A. Laatsch; Nils Becker; Franz Rinninger; Kerry‐Anne Rye; Ulrike Beisiegel (2004)
After internalization of triglyceride-rich lipoproteins (TRL) in hepatoma cells, TRL particles are immediately disintegrated in the early endosomal compartment. This involves the targeting of lipids and apoprotein B along the degradative pathway and the recycling of TRL-derived apoE through recycling endosomes. Re-secretion of apoE is accompanied by the concomitant association of apoE and cellular cholesterol with high-density lipoproteins (HDL). Since epidemiological data showed that apoE3 and apoE4 have differential effects on HDL metabolism, we investigated whether the intracellular processing of TRL-derived apoE4 differs from apoE3-TRL. In this study, we demonstrated by radioactive and immunofluorescence uptake experiments that cell-surface binding and internalization of TRL-derived apoE4 are increased compared with apoE3 in hepatoma cells. Pulse-chase experiments revealed that HDL-induced recycling, but not disintegration and degradation, of apoE4-enriched TRL is strongly reduced in these cells. Furthermore, impaired HDL-induced apoE4 recycling is associated with reduced cholesterol efflux. Studies performed in Tangier fibroblasts showed that apoE recycling does not depend on ATP-binding cassette transporter A1 activity. These studies provide initial evidence that impaired recycling of apoE4 could interfere with intracellular cholesterol transport and contribute to the pathophysiological lipoprotein profile observed in apoE4 homozygotes.